Sustainable tourism in Sleman, Indonesia: government communication strategy in empowering community through the development of tourism village - Prayudi Prayudi (Department of Communication Studies, Faculty of Social and Political Sciences Universitas, 2022)
Changing the mindset of the community and empowering them to develop tourism villages was always a challenge. It was even more challenging when the development of the tourism village was to adopt a sustainable development approach. The government needed to work together with other stakeholders if this policy was to succeed. This study examined how the Sleman Tourism Agency in Indonesia developed and planned a communication strategy to empower the community through the development of tourism villages based on the sustainable development approach. It used a qualitative research method to understand how the government communicated and empowered the community to develop a sustainable tourism village. The adoption of the public relations management process gave a detailed description of the communication strategy. There were four steps that the Sleman Tourism Agency had to follow in developing a communication strategy for community empowerment. Further, this study also identified the stakeholder that the government collaborated with through the ABCGM pentahelix model. There was an identification of the role of each relevant stakeholder in developing a tourism village. Finally, this paper argued that the Sleman Tourism Agency initiated a sustainable tourism village program but required communication and collaboration with other stakeholders in its development.